Knowledge management and innovation in Peninsular Malaysia - Tasmin, Rosmaini; Woods, Peter (2008)
Knowledge Management is frequently cited as one enabler of firm innovation especially among Western corporations.There is scant reported research that supports for such empirical links especially in the Malaysian context.There is a need for local research to address the KM practices, concepts, instruments, and effects.Using data from 149 Malaysian large manufacturing firms, a KM practices survey which comprises of five key domains are investigated.Measurement model analysis is engaged to confirm significant relations hips between variables and their respective KM factors.Subsequently, structural model analysis is applied to test theory of structural relation between KM and innovation.